Perancangan Mesin Roll Plat Listrik sebagai Peningkatan Efisiensi Kerja di Industri Manufaktur - Fathan Mubina; Amir Amir (Politeknik Negeri Jakarta, 2022)
Several engineering companies in Indonesia still use conventional type machines which, when viewed from the point of view of maintenance, repair, and performance, are still far behind. More than that, we use automatic machines. The first step in this research is to find some related literature that supports it. Then observe the machine that roughly corresponds to the shape of the design later. Then make the design of the electric plate roll machine design. After the design is understood, then plan the equations needed in the analysis of this research. If it is known the equation that will be made when the data is obtained, it can be calculated immediately. The calculation is not adequate, there may be improper equation planning. The final step is when the calculation is done, the conclusion can be determined immediately. Based on the stages of the design process for the automatic system aluminum plate roller machine, several conclusions can be drawn for this final project, including for the roller machine itself using an asymmetric plate roller type with two high mill roll arrangements because this type of machine is the most popular plate roll machine simple